Rancang Bangun Jaringan Internet Di Daerah Blankspot Dengan Memanfaatkan BTS Seluler Menggunakan Routerboard LTE Untuk Pelaksanaan Asessmen Nasional SMPN 6 Satu Atap Cimarga - M. Chandra Nugraha; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
SMPN 6 Satu Atap Cimarga is a school located in Kp. Lebuh, Sangiang Jaya Village, Cimarga District, Lebak Regency. Although the school is only 25 KM away from the capital city, internet access is very difficult to obtain because it is in a blankspot area. Difficult geographical conditions cause wireless infrastructure, optical fibre or cellular signals to be unreachable. The solution to overcome the blankspot is to use an LTE signal booster product from Mikrotik LTE4 routerboard category with the Embedded LTE Client LHG LTE Kit brand. The purpose of this research is to design and build an internet network at SMPN 6 One Roof Cimarga. Despite being in a blankspot location, the LTE signal can be received well by the RB LHG LTE antenna with EARFN parameter information: 1313 (band 3, bandwidth 20Mhz), RSRP -94 dBm, RSRQ -12.0 dB. SINR 3 dB and CQI 8. From these parameters the average bandwidth received on download is 37.38 Mbps, while for upload 20.81 Mbps. For the average latency, a value of 30ms was obtained.